Monitoring Alih Fungsi Lahan Sawah dan Pemetaan Status Petani Berbasis Remote Sensing dan Geographic Information System di Subak Kerdung dan Subak Cuculan Kota Denpasar - Panjaitan, Pranata Halasan; Lanya, Indayati; Bhayunagiri, Ida Bagus Putu (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024)DO - 10.24843/AJoAS.2024.v14.i02.p15, 2024)
Monitoring The Conversion of Rice Fields and Mapping The Status of Farmers in Subak Kerdung and Subak Cuculan, Denpasar City.   Subak Kerdung and Subak Cuculan are subaks that are included in the Green Open Space area of ??Denpasar City. The designation of this two subak as an open space areas for Denpasar City does not reduce the land conversion level. Therefore, it is necessary to have more protection by determining the area for Sustainable Food Agricultural Land (SFAL). Based on Government Regulation No. 25 of 2012, the preparation of SFAL needs to be equipped with a database, some of which are data on human resources and farmer status. This study aims to create a map of land-use change (2012-2021), a map of the distribution pattern of farmer status, and a human resources database. This study uses image analysis methods as well as surveys and mapping. The research stages include literature study, interpretation of satellite imagery, field surveys, image reinterpretation, and mapping and preparation of information systems. The results showed that for nine years, there was a conversion of 66.61 ha in Subak Kerdung and 22.62 ha in Subak Cuculan. The number of farmers in Subak Kerdung is 133 people, 121 people are sharecroppers with a total land area of ??93.2 (91.75%), and 18 people are owner farmers with a total land area of ??8.47 ha (8.25%). The number of farmers in Subak Cuculan was 24 people; 22 were sharecroppers with a total land area of ??7.43 ha (84.24%). Owner farmers opened two people with a total arable area of ??1.39 ha (15.76%). Farmers in Subak Kerdung and Subak Cuculan dominate the productive age (31-60 years). The average size of land cultivated by farmers in Subak Kerdung is 0.76 ha/person, and in Subak Cuculan is 0.36 ha/person. The results of this study are expected to be used by the Denpasar city government as a basis for evaluating and enforcing the law and as a reference for determining SFAL in Subak Kerdung and Subak Cuculan.